Case Study on the Impact of Artificial Light on Lighting Performance Quality for Architecture Studios - Adnan, N. A.; Sujali, N. S.; Md Amin, N. D. (International Journal of Integrated Engineering, 2021)
A well-lit learning space is crucial to ensure the comfort of its occupants, especially for an architecture student who spends long hours in a studio to design, sketch, draw and build prototypes. This paper presents the results from a study conducted on the illuminance level of the architecture studios in the city campus of Universiti Tun Hussein Onn Malaysia (UTHM), Malaysia that were once laboratories. Measurements had been done using the Lux meter. Illuminance contours were generated using SigmaPlot and Dialux software for all the five rooms and compared with the requirements stipulated in the Malaysian Standard, Australia/New Zealand Standard and Illumination Engineering Society of North America (IESNA) standard for a room with similar function. A survey was also conducted among undergraduate architecture students who were using the studios daily to gauge their perception on the lighting condition and comfort level. The outcome of this study can be considered for future architecture studio lighting design to improve the students’ learning experience.